How Infants and Young Children Learn About Food: A Systematic Review - Mura Paroche, Manon; Caton, Samantha J.; Vereijken, Carolus M. J. L.; Weenen, Hugo; Houston-Price, Carmel (Frontiers in Psychology, 2017)
Early childhood is a critical time for establishing food preferences and dietary habits. In order for appropriate advice to be available to parents and healthcare professionals it is essential for researchers to understand the ways in which children learn about foods. This review summarizes the literature relating to the role played by known developmental learning processes in the establishment of early eating behavior, food preferences and general knowledge about food, and identifies gaps in our knowledge that remain to be explored. A systematic literature search identified 48 papers exploring how young children learn about food from the start of complementary feeding to 36 months of age. The majority of the papers focus on evaluative components of children’s learning about food, such as their food preferences, liking and acceptance. A smaller number of papers focus on other aspects of what and how children learn about food, such as a food’s origins or appropriate eating contexts. The review identified papers relating to four developmental learning processes: 1. Familiarization to a food through repeated exposure to its taste, texture or appearance. This was found to be an effective technique for learning about foods, especially for children at the younger end of our age range. 2. Observational learning of food choice. Imitation of others’ eating behavior was also found to play an important role in the first years of life. 3. Associative learning through flavor-nutrient and flavor-flavor learning. Although the subject of much investigation, conditioning techniques were not found to play a major role in shaping the food preferences of infants in the post-weaning and toddler periods. 4. Categorization of foods. The direct effects of the ability to categorize foods have been little studied in this age group. However, the literature suggests that what infants are willing to consume depends on their ability to recognize items on their plate as familiar exemplars of that food type.